2020
DOI: 10.1101/2020.10.06.328948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Automated CUT&Tag profiling of chromatin heterogeneity in mixed-lineage leukemia

Abstract: Acute myeloid and lymphoid leukemias often harbor chromosomal translocations involving the Mixed Lineage Leukemia-1 gene, which encodes the KMT2A lysine methyltransferase. The most common translocations produce in-frame fusions of KMT2A to trans-activation domains of chromatin regulatory proteins. Here we develop a strategy to map the genome-wide occupancy of oncogenic KMT2A fusion proteins in primary patient samples regardless of fusion partner. By modifying the versatile CUT&Tag method for full automatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…2d). Notably, H3K36me3 was insufficient to separate cell types (32.3% efficiency), consistent with previous observations in single cell data and with the relative uniformity of H3K36me3 enrichment across different cell types 32 . An analysis of the 248 most informative enriched features for cell type distinction based on their values in the Singular Value Decomposition (SVD) input to UMAP showed that 100% of them were H3K27me3 features, consistent with its near-perfect distinction of highly dissimilar cell-type specific clusters (Supplementary Fig.…”
Section: Main Textsupporting
confidence: 90%
“…2d). Notably, H3K36me3 was insufficient to separate cell types (32.3% efficiency), consistent with previous observations in single cell data and with the relative uniformity of H3K36me3 enrichment across different cell types 32 . An analysis of the 248 most informative enriched features for cell type distinction based on their values in the Singular Value Decomposition (SVD) input to UMAP showed that 100% of them were H3K27me3 features, consistent with its near-perfect distinction of highly dissimilar cell-type specific clusters (Supplementary Fig.…”
Section: Main Textsupporting
confidence: 90%
“…pA-Tn5-based strategies profile histone modifications with high sensitivity and throughput, but requires optimizing experimental conditions to reduce the intrinsic affinity of Tn5 to open chromatin regions, especially when studying repressive chromatin states (Bartosovic et al, 2021;Harada et al, 2019;Janssens et al, 2020;Kaya-Okur et al, 2019;Wang et al, 2019;Wu et al, 2021). pA-MNase-based methods profile histone modifications with high sensitivity, and have robust detection of modifications associated with euchromatic regions as well as heterochromatic regions, but has generally less throughput compared with Tn5-based methods (Hainer et al, 2019;Ku et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatives to ChIP (Schmid et al, 2004) circumvent this pulldown by using antibody tethering of either protein-Amicrococcal nuclease (pA-MNase) (Ku et al, 2019;Skene and Henikoff, 2017) or protein-A-Tn5 transposase (Harada et al, 2019;Kaya-Okur et al, 2019), improving signal-to-noise by cutting only at specific sites of the genome. Although these tethering-based strategies have enabled large-scale profiling of histone modifications in single cells (Bartosovic et al, 2021;Janssens et al, 2020;Wu et al, 2021), they generally do not enrich for different cell types, making it difficult to dissect chromatin regulation in rare cell types, such as hematopoietic stem and progenitor cells in the bone marrow.…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale efforts characterizing different histone modifications in a variety of cell populations commonly use chromatin immunoprecipitation followed by sequencing (ChIP-seq) 10,11,[13][14][15][16] . Alternative strategies to ChIP-seq based on enzyme tethering (chromatin immunocleavage, ChIC) have reduced the background signal in profiling the epigenome 17 , and have enabled single-cell profiling of histone modifications [1][2][3][4][5][6][7][8][9]12 . Tethering strategies involve incubating cells with an antibody against a histone modification of interest, which then tethers either protein A-MNase 1,3,9,12 or protein A-Tn5 2, 4-8 fusion protein to generate targeted fragments in single cells.…”
Section: Introductionmentioning
confidence: 99%
“…
Recent advances have enabled mapping of histone modifications in single cells [1][2][3][4][5][6][7][8][9][10][11][12] , but current methods are constrained to profile only one histone modification per cell. Here we present an integrated experimental and computational framework, scChIX (single-cell chromatin immunocleavage and unmixing), to map multiple histone modifications in single cells.
…”
mentioning
confidence: 99%